Kazakh poetry of 19 century from sufi perspective (Journal of Oriental Studies, 2016)
The article considers Kazakh poetry of 19 century from sufi perspective. Review of Kazakh poets’ art in that period enables to claim of their good awareness of hikmets of Kozha Akhmet Yassayi, a turk sufi poet, consequently Kazakh poets should had known of sufi motives and its symbols. Even though sufi thesaurus was applied widely it had been transformed in its meaning and interpretation.
Keywords: Sufi teachings; thesaurus; similarity; interpretation